Genome‐Wide Assessment of the Binding Effects of Artificial Transcriptional Activators by High‐Throughput Sequencing. (25th August 2016) - Chandran, Anandhakumar; Syed, Junetha; Li, Yue; Sato, Shinsuke; Bando, Toshikazu; Sugiyama, Hiroshi
Abstract: One of the major goals in DNA‐based personalized medicine is the development of sequence‐specific small molecules to target the genome. SAHA‐PIPs belong to such class of small molecule. In the context of the complex eukaryotic genome, the differential biological effects of SAHA‐PIPs are unclear. This question can be addressed by identifying the binding regions across the genome; however, it is a challenge to enrich small‐molecule‐bound DNA without chemical crosslinking. Here, we developed a method that employs high‐throughput sequencing to map the binding area of small molecules throughout the chromatinized human genome. Analysis of the sequenced data confirmed the presence of specific binding sites for SAHA‐PIPs from the enriched sequence reads. Mapping the binding sites and enriched regions on the human genome clarifies the reason for the distinct biological effects of SAHA‐PIP. This approach will be useful for identifying the function of other small molecules on a large scale. Abstract : Uncrossed : Effects of artificial transcription‐activating small molecules binding to the human genome. Our reported SAHA PIP library showed unique gene‐set activation. But the mechanism is uncertain with the complex human genome. Therefore, we developed a high‐throughput sequencing method to address this without crosslinking the small molecules.